Pengaruh Literasi Perpajakan, Moral Pajak dan Insentif Pajak Terhadap Kepatuhan Wajib Pajak UMKM di Kabupaten Tana Toraja - Westerini Lusdani; Srisetyawanie Bandaso; Winta Panimba (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The Influence of Tax Literacy. Tax Morale and Tax Incentives on MSME Taxpayer Compliance in Tana Toraja Regency. The aim of this research is to find out whether tax literacy. Tax morale and tax incentives influence MSME taxpayer compliance in Tana Toraja Regency. The data collection procedures for this research are: Questionnaire. The analysis technique uses multiple linear regression tests. The partial test results (t test) show that the tax literacy variable influences the mandatory compliance of MSMEs in Tana Toraja Regency, the tax moral variable influences the compliance of MSME taxpayers in Tana Toraja Regency and tax incentives influence the compliance of MSME taxpayers in Tana Toraja Regency. Meanwhile, the results of simultaneous testing (F test) show that the variables of tax literacy, tax morale and tax incentives influence MSME taxpayer compliance in Tana Toraja Regency